Effect of storage temperature on bacterial count in commercial pasteurised milk - Ahmad Murad, Mohamad Fiddezuan (2017)
Awareness of consumer on proper handling and storing are not virtuous, milk are left at certain temperature without knowing the quality of the milk might be altered. A study is done, to investigate the effect of storage temperature and time on bacterial count of commercial pasteurise milk. This study had been conducted at Dairy Science Laboratory, Department of Animal Science, Faculty of Agriculture, UPM. For the first replication (n=8), total of eight commercial milk (300ml/pack) were used. These milk samples were stored in ice box (4ºC) before undergoing respective treatments; 4ºC (control), 21ºC (average air-condition room), 27ºC (average room temperature; humidity <70%) and 34ºC (average hot-day temperature). Factorial experiment, Completely Randomized Design (CRD) was used for this study. In determining the present of Pseudomonas sp, the colour of the agar change from pink to gold and brownish in colour. This indicating the presence of non-lactose fermentative bacteria which include Salmonella sp., Shigella sp., Proteus sp. and Pseudomonas aeruginosa. Second parameter are on the presence of the lactic acid bacteria in commercial milk. It shown that, there are significant effect of temperature and time on the growth of bacteria (P<0.05). Log mean of bacterial colony for temperature 4oC, 23oC, 27oC and 34oC are 4.81, 14.90, 20.06 and 30.70 respectively. It show, temperature 34oC are highly significant compare to other value of treatment follow by temperature 27oC, 23oC, and 4oC. It can be concluded that there is no significant effect of temperature and time on the growth of Pseudomonas sp. Also, temperature and time are highly significant to the growth of lactic acid bacteria in commercial milk